2011
DOI: 10.1099/vir.0.032839-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting antigenic sites on the foot-and-mouth disease virus capsid of the South African Territories types using virus neutralization data

Abstract: Foot-and-mouth disease virus (FMDV) outer capsid proteins 1B, 1C and 1D contribute to the virus serotype distribution and antigenic variants that exist within each of the seven serotypes. This study presents phylogenetic, genetic and antigenic analyses of South African Territories (SAT) serotypes prevalent in sub-Saharan Africa. Here, we show that the high levels of genetic diversity in the P1-coding region within the SAT serotypes are reflected in the antigenic properties of these viruses and therefore have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 53 publications
5
62
0
Order By: Relevance
“…The fact that the viral RNA can be made infectious in the absence of other components of the virion (reverse genetics) opened the theoretical possibility of genetically engineer-ing new viruses from in vitro-generated RNA molecules [24,27]. The introduction of specific mutations into the cloned genomes of viruses has allowed the manipulation of the biological prop-erties of field and laboratory strains and presents a promising avenue for the design of safe and effective vaccines [28][29][30]. We have structurally-engineered recombinant SAT viruses, containing desirable antigenic determinants and cell adaptation phenotypes [28,31,32] providing the proof-of-concept to rationally design viruses with the desired biological properties of a good vaccine strain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that the viral RNA can be made infectious in the absence of other components of the virion (reverse genetics) opened the theoretical possibility of genetically engineer-ing new viruses from in vitro-generated RNA molecules [24,27]. The introduction of specific mutations into the cloned genomes of viruses has allowed the manipulation of the biological prop-erties of field and laboratory strains and presents a promising avenue for the design of safe and effective vaccines [28][29][30]. We have structurally-engineered recombinant SAT viruses, containing desirable antigenic determinants and cell adaptation phenotypes [28,31,32] providing the proof-of-concept to rationally design viruses with the desired biological properties of a good vaccine strain.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of specific mutations into the cloned genomes of viruses has allowed the manipulation of the biological prop-erties of field and laboratory strains and presents a promising avenue for the design of safe and effective vaccines [28][29][30]. We have structurally-engineered recombinant SAT viruses, containing desirable antigenic determinants and cell adaptation phenotypes [28,31,32] providing the proof-of-concept to rationally design viruses with the desired biological properties of a good vaccine strain. Several studies have shown that inter-serotype chimeric vaccines successfully induce protective immune responses and protect FMD host species against live virus challenge [26,30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the vaccines provide only short-lived protection and the virus occurs as seven clinically indistinguishable serotpyes (O, A, C, Asia1 and three South African Territories serotypes: SAT1, SAT2 and SAT3), each of which has multiple, constantly evolving sub-types (Knowles & Samuel, 2003). Viruses belonging to the SAT serotypes display appreciably greater genomic and antigenic variation compare to serotype A and O viruses (Bastos et al, 2001;Bastos et al, 2003;Maree et al 2011), possibly due to their long term maintenance within African buffalo (Syncerus caffer). Constant surveillance of circulating strains is required to ensure that vaccine stocks remain effective.…”
Section: Introductionmentioning
confidence: 99%
“…The antigenic sites Ia and Ib of SAT1 viruses, for example, involve residues on both sides of the RGD motif in the G-H loop (Grazioli et al, 2006). In addition, plotting the observed variant amino acid residue on a model of the capsid pentamer of ZIM/7/83 indicated that the proposed epitope would be surface exposed and this position coincides with an antigenic region predicted by Reeve et al (2010) and Maree et al (2011) on ZIM/7/83. Added to this, the region has previously been identified as an antigenic area in the SAT2 viruses RHO/1/48 (Crowther et al, 1993b), as well as in ZIM/5/81 (Grazioli et al, 2006).…”
mentioning
confidence: 99%